Southeast Asia in the ancient Indian Ocean World; Combining historical linguistic and archaeological approaches - Hoogervorst, Tom G. (UI Scholars Hub, 2014)
This PhD dissertation examines the role of insular Southeast Asia in the trans-regional networks of maritime trade that shaped the history of Indian Ocean. The work brings together data and approaches from archaeology, historical linguistics and other disciplines, proposing a reconstruction of cultural and linguistic contact between Southeast Asia and its maritime neighbours to the west in order to advance our historical understanding of this part of the world. Numerous biological, commercial and technical items are examined. The study underlines that the analysis of lexical data is one of the strongest tools to detect and analyse contact between two or more speech communities. It demonstrates how Southeast Asian products and concepts were mainly dispersed by speakers of Malay varieties, although other communities played a role as well. Through an interdisciplinary approach, the study offers new perspectives on the role of insular Southeast Asian agents on cultural dynamism and interethnic contact in the pre-modern Indian Ocean World.